Case report: Early onset Marin-Amat syndrome after receiving ChAdOx1 nCoV-19 vaccination - Tsai, Ping-Feng; Chen, Ying-Jen (Frontiers in Medicine, 2022)
While vaccination against COVID-19 is still ongoing, some rare adverse events temporally related to vaccinations have been reported, particularly with ChAdOx1 nCoV-19. Here, a 77-year-old male presented to our outpatient department with persistent ptosis of his left eye for 1 month. He initially received vaccination with ChAdOx1 nCoV-19 and developed symptoms of Bell's palsy 3 days later. He received a 14-day course of prednisolone, but the ptosis persisted. Marin-Amat syndrome was compatible with his symptoms of ptosis exacerbation during orbicularis oris exertion. A temporal correlation between ChAdOx1 nCoV-19 vaccination and Bell's palsy without infectious or autoimmune diseases was delineated. Further studies are needed to clarify the possible relationship between these two events.